Amino acid concentrations and protein metabolism of two types of rat skeletal muscle in postprandial state and after brief starvation - Holeček, M; Mičuda, S (Physiological research, 2017)
We have investigated amino acid concentrations and protein metabolism in musculus extensor digitorum longus (EDL, fast-twitch, white muscle) and musculus soleus (SOL, slow-twitch, red muscle) of rats sacrificed in the fed state or after one day of starvation. Fractional protein synthesis rates (FRPS) were measured using the flooding dose method (L-[3,4,5-3H]phenylalanine). Activities of two major proteolytic systems in muscle (the ubiquitin-proteasome and lysosomal) were examined by measurement of chymotrypsin like activity of proteasome (CTLA), expression of ubiquitin ligases atrogin-1 and muscle-ring-finger-1 (MuRF-1), and cathepsin B and L activities. Intramuscular concentrations of the most of non-essential amino acids, FRPS, CTLA and cathepsin B and L activities were in postprandial state higher in SOL when compared with EDL. The differences in atrogin-1 and MuRF-1 expression were insignificant. Starvation decreased concentrations of a number of amino acids and increased concentrations of valine, leucine, and isoleucine in blood plasma. Starvation also decreased intramuscular concentrations of a number of amino acids differently in EDL and SOL, decreased protein synthesis (by 31 % in SOL and 47 % in EDL), and increased expression of atrogin-1 and MuRF-1 in EDL. The effect of starvation on CTLA and cathepsin B and L activities was insignificant. It is concluded that slow-twitch (red) muscles have higher rates of protein turnover and may adapt better to brief starvation when compared to fast-twitch (white) muscles. This phenomenon may play a role in more pronounced atrophy of white muscles in aging and muscle wasting disorders.
Keywords: Muscle Proteins; aminokyseliny; Proteolysis; Proteasome Endopeptidase Complex; Male; proteolýza; Rats, Wistar; Lysosomes; proteasomový endopeptidasový komplex; potravinová deprivace; svalová vlákna typu II; svalové proteiny; Adaptation, Physiological; Ubiquitin-Protein Ligases; mužské pohlaví; ubikvitinligasy; SKP Cullin F-Box Protein Ligases; potkani Wistar; proteinligasy komplexu SCF; fyziologická adaptace; postprandiální období; ubikvitinace; Muscle Fibers, Slow-Twitch; Ubiquitination; Food Deprivation; lyzozomy; Time Factors; Animals; Postprandial Period; zvířata; časové faktory; Tripartite Motif Proteins; Muscle Fibers, Fast-Twitch; svalová vlákna typu I; TRIM protein; Amino Acids